2013
DOI: 10.1371/journal.pone.0071799
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Risk for Metabolic Syndrome and Insulin Resistance Associated with Ovo-Lacto-Vegetarian Behavior in Female Buddhists: A Case-Control Study

Abstract: IntroductionThe association of vegetarian status with the risk of metabolic syndrome (MetS) is not clear. In Asia, Buddhists often have vegetarian behavior for religious rather than for health reasons. We hypothesize that the vegetarian in Buddhism is associated with better metabolic profiles, lower risk for the MetS and insulin resistance (IR).MethodsWe enrolled 391 female vegetarians (∼80% lacto-ovo-vegetarians) and 315 non-vegetarians from health-checkup clinics at a Buddhist hospital in Taiwan.ResultsThe v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 26 publications
2
50
1
13
Order By: Relevance
“…Numerous studies have shown that people consuming vegetarian and also vegan diet had lower high-density lipoprotein cholesterol levels compared with omnivorous healthy people. [29][30][31] Although the exact mechanism is not clear, a recent public-based study showed that Apo A-1 levels were significantly lower in vegan women than in their carnivorous peers when adjusted for body mass index. 32 As Apo A-1 is an important structural apolipoprotein of the high-density lipoprotein cholesterol molecule, diminished Apo A-1 levels might be a causative factor for lower highdensity lipoprotein cholesterol levels in vegetarians.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that people consuming vegetarian and also vegan diet had lower high-density lipoprotein cholesterol levels compared with omnivorous healthy people. [29][30][31] Although the exact mechanism is not clear, a recent public-based study showed that Apo A-1 levels were significantly lower in vegan women than in their carnivorous peers when adjusted for body mass index. 32 As Apo A-1 is an important structural apolipoprotein of the high-density lipoprotein cholesterol molecule, diminished Apo A-1 levels might be a causative factor for lower highdensity lipoprotein cholesterol levels in vegetarians.…”
Section: Discussionmentioning
confidence: 99%
“…2), as documented in the Japanese National Health and Nutrition Survey [139] and in the Korean National Health and Nutrition Examination Survey [140,141]. Vegetarian and vegan diets are commonly followed not only in India but also in other Asian countries and have recently gained popularity particularly among young women of childbearing age [142,143,144,145]. Vegetarian diets provide very little, and vegan diets provide basically no, preformed LC-PUFA.…”
Section: Recent Recommendations On Pre- and Postnatal Lc-pufa Supplymentioning
confidence: 99%
“…The prevalence of MetS tended to be lower (33•9 %) compared with non-vegetarian (47•9 %). Chiang et al (2013) (31) Case -control (n 706) Vegetarian (55 %) approximately 80 % Lacto-ovo Non-vegetarian ( (32) Case -control (n 202) Lacto-ovo-vegetarian (47 %) Non-vegetarian (53 %)…”
Section: Obesity and Insulin Resistancementioning
confidence: 99%